«Madame Gervaisais» by E. and J. Goncourt as a «mystical novel» - Таран, Зинаїда Михайлівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article discusses the new artistic style of the brothers E. and J. Goncourt in the writing of the novel «Madame Gervaisais». The «mysticism» of work appears on the different levels of novel structure: in a plot, composition, artistic conflict, figurativeness, language and style. Along with elements of naturalism and realism, other means of novel writing, in particular impressionism, are used in the novel. Realistically representing the tragic life of the main heroine Madame Gervaisais, the authors show that neither marriage, nor family, nor love of nature or art, which gave an impulse for development of the religious feelings of the heroine were able to fully compensate internal spiritual emptiness of her «artistic nature». The authors reveal the fanatical attitude of Madame Gervaisais to religion, which led to the loss of sense of reality, femininity, maternal feelings. The brothers E. and J. Goncourt disclosed the process of the spiritual destruction of the personality of woman and her tragedy in contemporary society, which is devoid of specific moral values and orientations. The main attention in the article is devoted to facilities of psychological analysis and elements of mysticism which reveal the complexity of the spiritual life of the heroine.